New Frontiers in the Study of Social Phenomena Cognition, Complexity, Adaptation - Cecconi, Federico (Springer International Publishing : Imprint: Springer, 2016)
This book studies social phenomena in a new way, by making judicious use of computer technology. The book addresses the entire spectrum of classic studies in social science, from experiments to the computational models, with a multidisciplinary approach. The book is suitable for those who want to get a picture of what it means to do social research today, and also to get an indication of the major open issues. The book is connected to a database of code for simulations, experimental data and allows to activate a subscription to a teaching tool using NetLogo, a programming language widely used in the social studies. The authors are researchers with first-hand experience research projects, both basic and applied. The work will be useful for those who want to understand more of the social, economic and political phenomena via computer applications.